1995
DOI: 10.1002/bjs.1800820245
|View full text |Cite
|
Sign up to set email alerts
|

Prospective trial comparing Lichtenstein with laparoscopic tension-free mesh repair of inguinal hernia

Abstract: A prospective study of 242 patients with inguinal hernia who underwent tension-free mesh repair by the laparoscopic transperitoneal (n = 121) or the open Lichtenstein (n = 121) technique was performed. There was no significant difference in operation time between the laparoscopic (median (range) 35 (20-90) min) and Lichtenstein (40 (20-90) min) procedures. Discharge within 24 h of operation was more common after laparoscopic surgery (89.3 per cent versus 48.7 per cent). Consequently, hospital stay was reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
26
1
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(33 citation statements)
references
References 8 publications
4
26
1
2
Order By: Relevance
“…However, several studies have demonstrated the advantages of the laparoscopic approach, including a reduced incidence of postoperative pain, and earlier return to activities when compared to both Shouldice and open mesh repairs [8,12,13]. This benefit has been noted specifically for unilateral repairs [3,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies have demonstrated the advantages of the laparoscopic approach, including a reduced incidence of postoperative pain, and earlier return to activities when compared to both Shouldice and open mesh repairs [8,12,13]. This benefit has been noted specifically for unilateral repairs [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have also been controlled trials that show no significant difference between open or laparoscopic repairs [8,12,13], even in one trial in which the surgeons performed only 10 repairs each prior to the study [8]. Day-case surgery began in our unit after approximately 300 repairs had already been done on inpatients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilson MS et al, the return to work was shorter in patients receiving laparoscopic repair (median 7 and 10 days, respectively) than Lichtenstein repair (14 and 21 days) (25) . Mike Liem et al observed the mean time to return to work in patients undergoing inguinal hernia repair and found it to be 14 and 21 days respectively for laparoscopic and open mesh repair groups (26) .…”
Section: Discussionmentioning
confidence: 98%
“…W~ihrend Payne et al[12] nach laparoskopischer Hernienreparation in der TAPP-Technik im Vergleich zur offenen Lichtenstein-Methode geringere Schmerzen und einen geringeren Analgetikabedarf fanden, konnten Wilson et al[21 ] zwischen beiden Verfahren diesbeztiglich keinen Unterschied feststellen. Auch Brooks[2] ermittelte beim Vergleich zwischen laparoskopischer TAPP-Methode mit der offenen Plug-und-Patch-Reparation etwas geringere Schmerzen und einen geringeren Schmerzmittelbedarf ffir das laparoskopische Verfahren, der Unterschied war jedoch nicht statistisch signifikant.…”
unclassified